OBSERVATIONS ON OPTIMUM HAULING SPEED OF PLANKTON NET FOR VERTICAL-HAUL COLLECTIONS - Srivastava, S P; Karamchandani, S J (Indian Journal of Fisheries, 2011)
The optimum speed of hauling of a vertical plankton net in order to catch highest quantity and quality of plankton in reservoirs is determined as a result of experiment